Incidental vs. non-incidental gallbladder cancer – a hospital-based clinicopathological study - Dash, Sashibhusan; Anirvan, Prajna; Samantaray, Sagarika; Rout, Niranjan; Ranjit, Manoranjan (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Most gallbladder cancers (GBCs) are discovered incidentally after routine cholecystectomy. The clinicopathological characteristics and prognostic implications of incidental gallbladder cancer (IGBC) versus non-incidental gallbladder cancer (NIGBC) is not known. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. During this study, clinicopathological details compared between incidental and non-incidental GBC groups included age, sex, clinical presentation, preoperative radiological diagnosis, surgical management, and macroscopic and microscopic features. The primary outcome of the study was difference in overall survival (OS) between IGBC and NIGBC. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Among 348 surgically treated patients, 56.6% weren’t preoperatively suspected of GBC. Macroscopic examination showed characteristic thickened gallbladder wall without mass lesion (IGBC) vs. clear mass lesion (NIGBC) on imaging. Interestingly, NIGBC had higher LVI (27% vs. 14%) and T stage (68% T2b/T3 vs. 47% T1b/T2a) despite lower margin involvement (p < 0.001). The OS for all patients was 12.2 months (median). Among patients who underwent surgery with curative intent, the median survival time was 21.4 months. However, within this group, NIGBC cases had a worse median survival (17 months) compared to IGBC cases (21 months). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Rising incidental GBC necessitates routine microscopic examination of all gallbladder specimens. Surgeons in high-risk areas should remain vigilant for GBC in patients with atypical clinical and ultrasound findings. Early detection and curative resection are paramount for long-term survival in gallbladder carcinoma, with IGBC potentially offering a survival benefit regardless of stage or tumor characteristics. Prospective studies including detailed pathology and molecular analysis are needed to confirm this observation.